Medicare coverage patterns favor non-invasive and minimally-invasive treatments of knee osteoarthritis compared to temporomandibular joint osteoarthritis. Issue 2 (4th March 2023) - Govind, Akshay; Ploussard, Danielle; Hoffman, Sydney; Zhang, Zhenzhen; Wu, Ying
ABSTRACT: Objective: To compare Medicare coverage patterns for treatments of knee osteoarthritis (OA) to those of temporomandibular joint (TMJ) OA. Methods: The International Classification of Diseases (ICD)-10 codes were used to identify knee OA, TMJ OA, and related diagnoses. The AAPC Coder was utilized to search for Medicare insurance coverage by state/district for the indicated CPT codes. The coverage for treatments of TMJ OA and knee OA was analyzed by Fisher's exact test. Results: There was a statistically significant difference in the coverage of physical therapy, massage therapy, and arthrocentesis for TMJ OA and knee OA. The current study showed that arthrocentesis was covered 100% in all states/districts for knee OA and 0% for TMJ OA. Conclusion: Medicare covers TMJ OA treatments to a lesser degree than knee treatments. Documentation of this discrepancy serves as an important first step in advocating for improvements in coverage, and subsequently, in access to care.